Replacement of bovine milk with vegetable milk: Effects on the survival of probiotics and rheological and physicochemical properties of frozen fermented dessert - Aboulfazli, F.; Baba, A.S.; Misran, M. (Blackwell Publishing, 2015)
In this study, frozen fermented desserts containing Lactobacillus acidophilus (La-05; L) and Bifidobacterium bifidum (Bb-12; B), were made from bovine (W), soya (S), coconut (C) and composite (i.e. combinations of coconut or bovine milks with soya milk) milks. The changes in frozen dessert eating qualities and the survival of added microbes were evaluated. The highest viscosity and melting resistance, and the lowest total sensory scores, were found in the products made using soya milk. After 90-day storage at −20 °C, the highest survival percentage of La-05 was found in the products made using coconut milk (CL); and for Bb-12, it was found in the products made using soya milk, coconut milk and a 25:75 blend of soya milk and coconut milk respectively ( samples SB, CB and SC3B) SB, SCB and CB samples.